ANOMALOUS ERRORS IN DETERMINING FOCUS COORDINATES EARTHQUAKES AND SUGGESTIONS FOR THEIR ELIMINATION - G. K. Aslanov; T. G. Aslanov; U. A. Musaeva (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives The aim of the study is to develop a method for estimating the speed of seismic waves in different directions of propagation and by taking into account the dimensions of the focus, reducing the error in determining the coordinates of the hypocenter. Method To find the hypocenter of the earthquake, the data of the seismic wave velocities, the differences in the times of arrival of seismic waves on seismic sensors and the error in determining the time difference are used. The data with an error determine the coordinates of the hypocenter using information from various combinations of seismic sensors. Processing the resulting array of coordinates, estimates the seismic wave velocities / or determines the spatial shape of the earthquake source and the coordinates of the hypocenter. According to the coordinates of the cinema center, the differences in the travel time of seismic waves are corrected and the distances to the seismic sensors are refined. Results After preliminary determination of the coordinates and shape of the earthquake source, if there are a large number of seismic sensors, it is possible to clarify the coordinates of the earthquake hypocenter taking into account the recommendations given in the works. Conclusion Using the proposed method implies the presence of a large number of sensors to determine the complex shape, the earthquake source.